Implementasi Penggunaan Media Flashcard dalam Pembelajaran Vocabulary pada Siswa di SMK PGRI 1 Tambun Selatan Bekasi - Erik Sarika; Joni Tesmanto (Neolectura, 2021)
This study aims to determine students' perceptions of the card media used by teachers of SMK PGRI 1 Tambun Selatan Bekasi in teaching. This research uses descriptive research. The population of this study was the second grade students of SMK PGRI 1 Tambun Selatan Bekasi in the 2020/2021 academic year and the research sample is class X AK. The researcher used the sampling technique. The techniques used to obtain data are: first, collecting data from students answering the questionnaire and lastly, drawing conclusions based on the data. The final result of the analysis shows that there are positive statements about the use of card media in teaching and learning by teachers, are positive statements of students found in the practical category 48.75% are students answered very well (VG), 39.11% good (G), 2.94% average average, 0.29% poor (B), and none very bad (VG). For negative statements, students found in the practical category 0.29% were students answered very strongly (VG), 3.82% good (G), 25.30% average, 38.53% bad (B), and 32.06% very bad (VB). It is evidenced by the results of the average score of the student questionnaire is 85.26, the majority of students choose the good from the positive statement and choose the bad in the negative statement about the use of card media in teaching English.